Home Advantage and Sports Performance: Evidence, Causes and Psychological Implications (2013)
Home advantage in competitive sports is well documented despite some contradictory results. Previous studies have identified 5 main causes of home advantage in competitive sports: crowd, familiarity, travels, rules and territoriality. Moreover, several studies have proposed the influence of these factors over psychological and behavioral states in athletes, coaches and referees. The present review summarizes the available scientific evidences about home advantage in sport and tries to identify the environmental and psychological causes of this phenomenon.